2016
DOI: 10.1111/imm.12667
|View full text |Cite
|
Sign up to set email alerts
|

Functional interleukin‐33 receptors are expressed in early progenitor stages of allergy‐related granulocytes

Abstract: SummaryInterleukin-33 (IL-33) induces T helper type 2 (Th2) cytokine production and eosinophilia independently of acquired immunity, leading to innate immunity-mediated allergic inflammation. Allergy-related innate myeloid cells such as eosinophils, basophils and mast cells express the IL-33 receptor (IL-33R), but it is still unknown how IL-33 regulates allergic inflammation involving these cells and their progenitors. Here, we revealed that the functional IL-33R was expressed on eosinophil progenitors (EoPs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
(67 reference statements)
2
18
0
Order By: Relevance
“…d), however, in PBS‐treated control mice, representing homeostatic conditions, anti‐IL‐5 treatment led to a significant decrease of circulating eosinophils, as previously shown . Indeed, consistent with our results, two recent studies reported elevated IL‐5 in the serum of IL‐33‐treated mice and where IL‐33‐induced eosinophilia was impaired upon neutralization of IL‐5 . However, interestingly, we also found that the expression of eotaxin‐2/CCL24 in serum (Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…d), however, in PBS‐treated control mice, representing homeostatic conditions, anti‐IL‐5 treatment led to a significant decrease of circulating eosinophils, as previously shown . Indeed, consistent with our results, two recent studies reported elevated IL‐5 in the serum of IL‐33‐treated mice and where IL‐33‐induced eosinophilia was impaired upon neutralization of IL‐5 . However, interestingly, we also found that the expression of eotaxin‐2/CCL24 in serum (Fig.…”
Section: Resultssupporting
confidence: 92%
“…acquired IL5R α expression), suggesting a fine‐tuned interplay between IL‐33 and IL‐5 in hematopoietic differentiation, which has been described in further detail by others . In a recent study, ST2 expression in mature granulocytes including eosinophils, basophils and mast cells, was compared with the expression of the ST2 receptor in precursor cells . Eosinophil progenitors, basophil progenitors and mast cell progenitors were all found to express ST2 at higher levels than the mature cells.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…IL‐33 promotes eosinophil‐mediated inflammation and our lab has recently demonstrated that Siglec‐8 engagement on IL‐33‐primed eosinophils results in apoptosis . Lately it has been shown that eosinophil progenitors express a functional IL‐33 receptor capable of producing pro‐inflammatory cytokines at levels that far surpass those observed in mature eosinophils …”
Section: Cell Surface Receptorsmentioning
confidence: 99%